2017
DOI: 10.1002/jsfa.8253
|View full text |Cite
|
Sign up to set email alerts
|

Maternal cinnamon extract intake during lactation leads to sex‐specific endocrine modifications in rat offspring

Abstract: The present study demonstrates that maternal cinnamon intake during lactation promotes mild changes in dams and can trigger sex-specific metabolic programming in pups that lasts into adulthood. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
(136 reference statements)
0
1
0
Order By: Relevance
“…Cinnamon is a common spice that is used worldwide and has been widely studied as a nutraceutical for the management of insulin resistance, obesity and dyslipidemia (Rafehi et al 2012, Medagama 2015. According to the results of human, animal or in vitro studies, cinnamon and its active biological compounds interfere with the biosynthesis or action of many hormones, such as insulin, glucagon-like peptide-1 (GLP1), ghrelin and leptin (Hlebowicz et al 2009, Rafehi et al 2012, Camacho et al 2015, Lopes et al 2015, Medagama 2015, Bento-Bernardes et al 2017. In this context, a study showed that rats supplemented with a water extract of cinnamon exhibited lower serum T3 levels accompanied by unaltered serum T4 and TSH levels.…”
Section: Cinnamonmentioning
confidence: 99%
“…Cinnamon is a common spice that is used worldwide and has been widely studied as a nutraceutical for the management of insulin resistance, obesity and dyslipidemia (Rafehi et al 2012, Medagama 2015. According to the results of human, animal or in vitro studies, cinnamon and its active biological compounds interfere with the biosynthesis or action of many hormones, such as insulin, glucagon-like peptide-1 (GLP1), ghrelin and leptin (Hlebowicz et al 2009, Rafehi et al 2012, Camacho et al 2015, Lopes et al 2015, Medagama 2015, Bento-Bernardes et al 2017. In this context, a study showed that rats supplemented with a water extract of cinnamon exhibited lower serum T3 levels accompanied by unaltered serum T4 and TSH levels.…”
Section: Cinnamonmentioning
confidence: 99%
“…It has long been used as a spice and in traditional herbal medicines. Available evidence suggests that cinnamon has beneficial effects on diabetes management [3]. Multiple mechanisms have been proposed by which cinnamon improves diabetes, including enhancing insulin sensitivity through insulin receptor signaling, inhibiting the activity of carbohydrate-digesting enzymes, inhibiting glucose transport, delaying gastric emptying, and blocking glucose absorption [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Available evidence suggests that cinnamon has beneficial effects on diabetes management 27 . Multiple mechanisms have been proposed by which cinnamon improves diabetes, including enhancing insulin sensitivity through insulin receptor signaling, inhibiting the activity of carbohydrate-digesting enzymes, inhibiting glucose transport, delaying gastric emptying, and blocking glucose absorption 28 . The liver plays a crucial role in glucose metabolism.In fact, one study in 84 people with polycystic ovary syndrome (PCOS) found that taking 1,500 milligrams (mg) of cinnamon daily led to a significant increase in antioxidant blood levels after 8 weeks 29 .Antioxidants are important because they help the body reduce oxidative stress, a type of damage to cells that is caused by harmful free radicals 30 .One study showed that consuming 1 gram (g) of cinnamon extract daily for 12 weeks reduced fasting blood sugar levels and improved markers of oxidative stress in people with type 2 diabetes 31 .…”
Section: Cinnamonmentioning
confidence: 99%